IMPLEMENTASI KEBIJAKAN OBAT NASIONAL (KONAS) DI ERA DIGITAL : LITERATUR REVIEW - Novega Diyan Al Amanah; Nevi Nur Fitriasari; Muhammad Anugerah Wijaya (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
The e-catalogue policy is part of Indonesia’s National Drug Policy (KONAS) aimed at improving drug procurement efficiency in the National Health Insurance (JKN) era. This study analyzed the effectiveness of e-catalogue implementation on procurement efficiency, price transparency, and drug stock availability in healthcare facilities. A literature review with a descriptive qualitative approach was conducted using articles from Google Scholar, PubMed, and ScienceDirect published between 2019–2025. Data were analyzed through content analysis and narrative synthesis. The findings showed that e-catalogue implementation improved price transparency, standardized drug prices, and accelerated procurement processes. However, challenges such as delayed distribution, limited human resources, weak inventory management, and regional implementation disparities still affected drug availability. Strengthening distribution systems, information technology integration, and pharmaceutical workforce capacity are needed to optimize national drug policy implementation in the digital era.